Subdural Pharmacotherapy for the Treatment of Intractable Focal Neocortical Epilepsy - Ludvig, Nandor (Drug Delivery Letters, 2012)
The Subdural Pharmacotherapy Device (SPD) is an experimental medical implant for the treatment of intractable focal neocortical epilepsy. The device performs spatially and temporally controlled administration of seizurepreventing drugs into the subarachnoid space overlaying the neocortical seizure focus or foci. This is accomplished with the use of a multifunction subdural strip, through which the device periodically (a) delivers drugs to achieve local treatment without systemic side-effects, (b) receives electrophysiological feedback on this local treatment so that neither ineffective nor toxic drug administration can take place, and (c) removes local cerebrospinal fluid (CSF) containing tissue reaction cells and proteins to maintain adequate transmeningeal drug diffusion into the seizure focus for long periods. The present drug-of-choice that emerged for this device is muscimol, a potent GABAA receptor agonist. Experimental data obtained in freely-behaving nonhuman primates implanted with the muscimol-delivering SPD showed that this treatment can fully prevent focal neocortical seizures for many months without tolerance. Neurological symptoms or behavioral abnormalities did not develop during SPD-use, for at least a year. Based on all accumulated data, the muscimol-delivering SPD seems to have clinical potential. The present device needs to be adapted to human use, and its safety and antiepileptic efficacy need to be confirmed in further studies. Should this effort succeed, it may well lead to a new therapeutic option for at least a subgroup of the approximately 150,000 US patients who suffer from otherwise untreatable focal neocortical epilepsy.
Keywords: muscimol